Assessment of plastic debris in remote islands of the Andaman and Nicobar Archipelago, India. (February 2020) - S., Krishnakumar; S., Anbalagan; K., Kasilingam; P., Smrithi; S., Anbazhagi; S., Srinivasalu
Abstract: An attempt was made in during August 2018 to study the plastic debris present in beach sediments at the remote islands of the Andaman and Nicobar Archipelago, India. The maximum number of plastic debris was noticed in the North and Middle Andaman Island sector and the Nicobar Island sector. White, irregular shaped polyethylene and polypropylene debris were the predominant plastic varieties found in the study area. The plastic litters disposed in the marine environment could be carried away by currents, which then circulate around the island and finally reach the coastal areas of the Andaman and Nicobar Archipelago. The plastic litter was contributed from tourist, shipping activities and improper handling of solid wastes. Highlights: The maximum number of plastic debris was noticed in the North, Middle Andaman island and Nicobar Island sector. White, irregular shaped polyethylene and polypropylene were the predominant plastic varieties found in the study area. The plastic litter was contributed from tourist, shipping activities and improper handling of solid wastes.